(untitled) (Jurnal Manajemen Bisnis, 2026)
This study aims to determine whether there is a significant difference in the financial performance of public banking companies in Indonesia before and after mergers and acquisitions (M&A). The main focus of the study is to measure the effectiveness of M&A in improving financial performance through certain financial ratios. This study uses a quantitative approach with a comparative design. The sample consists of six public banking companies that conducted M&A during the period 1994–2022, selected through purposive sampling. Data were obtained from published financial reports. The variables analyzed included liquidity ratios (current ratio and quick ratio) and profitability ratios (return on equity and net profit margin). Data analysis techniques used the Paired Sample t-Test and the Wilcoxon Test to examine differences in financial performance two years before and two years after M&A. The results show no significant differences in the Current Ratio, Quick Ratio, Return on Equity, and Net Profit Margin before and after mergers and acquisitions. This indicates that M&A activities have not had a tangible impact on improving short-term financial performance. This study provides practical contributions for company management and investors in evaluating the effectiveness of M&A strategies. These findings can also serve as a basis for further research to expand the scope of variables and observation periods.